Modelling the impact of a highly potent Plasmodium falciparum transmission-blocking monoclonal antibody in areas of seasonal malaria transmission - Challenger,JD; van,Beek SW; Heine,RT; van,der Boor SC; Charles,GD; Smit,MJ; Ockenhouse,C; Aponte,JJ; McCall,MBB; Jore,MM; Churcher,TS; Bousema,T (Journal of Infectious Diseases, 2023)
Transmission-blocking interventions can play an important role in combatting malaria worldwide. Recently, a highly potent Plasmodium falciparum transmission-blocking monoclonal antibody (TB31F) was demonstrated to be safe and efficacious in malaria-naive volunteers. Here we predict the potential public health impact of large-scale implementation of TB31F alongside existing interventions. We developed a pharmaco-epidemiological model, tailored to two settings of differing transmission intensity with already established insecticide-treated nets and seasonal malaria chemoprevention interventions. Community-wide annual administration (at 80% coverage) of TB31F over a three-year period was predicted to reduce clinical incidence by 54% (381 cases averted per 1000 people per year) in a high-transmission seasonal setting, and 74% (157 cases averted per 1000 people per year) in a low-transmission seasonal setting. Targeting school-aged children gave the largest reduction in terms of cases averted per dose. An annual administration of transmission- blocking monoclonal TB31F may be an effective intervention against malaria in seasonal malaria settings.